Relationship Between of the Sodium Intake and Central Obesity with the Incidence of Hypertension Among the Community in Mulyoarjo Village, Lawang District, Malang Regency, in 2025 - Aprilawati, Dwi; Susanti, Dwi; Atika, Atika; Bima, Ralvinzah Cahya Satriya; Sumiati, Sumiati (Syntax Literate, 2025)
Data from the National Basic Health Research (Riskesdas) show that the national prevalence of hypertension was 28.5% in 2013 and increased to 34.11% in 2018. Preliminary research conducted in Mulyoarjo Village, Lawang Subdistrict, Malang Regency, found that out of 30 respondents interviewed, 27 people (90%) suffered from hypertension, and 23 of them were obese, consisting of 16 women (53.3%) and 7 men (23.3%) with central obesity. The population in this study consisted of individuals with hypertension aged 15–64 years residing in Mulyoarjo Village, Lawang Subdistrict, Malang Regency, East Java. The study used an analytical observational design with a cross-sectional approach. The independent variables were food additives and central obesity among hypertensive individuals of productive age in Mulyoarjo Village, Lawang Subdistrict, Malang Regency. The dependent variable was the incidence of hypertension in the same population. Data were collected using questionnaires distributed to residents in the study area, with a minimum sample size of 38 participants, determined using Fisher’s Z formula. Respondent characteristics were assessed using the Food Frequency Questionnaire (FFQ). Data were analyzed using the Chi-square test. Results obtained from the Food Frequency Questionnaire (FFQ) showed that, among 53 respondents, the majority (66%, or 35 individuals) had a low sodium intake. The Chi-square test results indicated no significant relationship between central obesity and hypertension (p > 0.05), as shown by a Chi-square correlation coefficient (p) of 0.054. Similarly, no significant relationship was found between sodium intake and hypertension (p = 0.682). Many factors influence hypertension, not only substances added to food and obesity, the main role is physical activity. Physical activity can suppress RAAS activation and reduce the risk of hypertension (Hall et al., 2015). Furthermore, physical exercise also contributes to reduced arterial stiffness and low-grade chronic inflammation, both of which play important roles in the pathogenesis of hypertension.